2016
DOI: 10.4103/0976-237x.177113
|View full text |Cite
|
Sign up to set email alerts
|

Dilated odontoma: A report of two cases from a radiological perspective

Abstract: Dilated odontoma is the most extreme form of dens invaginatus. The lesion appears as a roughly spherical mass that does not resemble a tooth but in a way appears tooth - like on radiographs due to somewhat similar radiodensity. The lesion is mostly spherical in appearance and hence the term “dilated.” Occasionally, we come across cases of simultaneous pathologies. Here, we report two cases of a dilated odontoma one of which is associated with dentigerous cyst and in other case dilated odontoma pushing the maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
3
0
3
Order By: Relevance
“…In the most recently published review of the literature, sixteen extracted type III dens invaginatus cases were reported [ 3 ]. Eight of these cases were classified as dilated odontoma [ 1 , 2 , 3 , 8 , 9 , 10 , 11 , 13 ], while the other four cases were published by Matsumoto and Seto [ 14 ]. A clinical synopsis of these cases is reported in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the most recently published review of the literature, sixteen extracted type III dens invaginatus cases were reported [ 3 ]. Eight of these cases were classified as dilated odontoma [ 1 , 2 , 3 , 8 , 9 , 10 , 11 , 13 ], while the other four cases were published by Matsumoto and Seto [ 14 ]. A clinical synopsis of these cases is reported in Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…In rare cases, the invagination may significantly dilate, impairing the normal development of the involved tooth [ 2 , 3 , 6 ]. In this condition, which is commonly reported as dilated odontoma, the involved tooth shows a doughnut-like circular-oval shape with a radiolucent interior [ 2 , 3 , 6 , 7 , 8 , 9 , 10 , 11 ]. Thus, dilated odontoma is considered the extreme and most severe form of dens invaginatus [ 2 , 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Por su parte, en el tipo III, el diente se muestra totalmente deformado, con una forma circular u ovalada, y presenta una zona radiolúcida; su interior es radiotransparente y muestra una sola estructura con tejido blando en el centro, con una expansión abultada y tuberosa de la raíz del diente afectado. La valoración inicial con una radiografía periapical revela tanto el tipo, la extensión y la complejidad morfológica del DI como las pérdidas óseas reales ( 3,8,11,14,22 ). Debido a que es una patología asintomática y de crecimiento lento, el DI suele ser diagnosticado por hallazgos radiográficos obtenidos mediante estudios panorámicos ( 3,8,21 ).…”
Section: Imagenología Del Diente Invaginadounclassified
“…La valoración inicial con una radiografía periapical revela tanto el tipo, la extensión y la complejidad morfológica del DI como las pérdidas óseas reales ( 3,8,11,14,22 ). Debido a que es una patología asintomática y de crecimiento lento, el DI suele ser diagnosticado por hallazgos radiográficos obtenidos mediante estudios panorámicos ( 3,8,21 ). La tomografía computarizada de haz cónico (TCHC) es considerada como la técnica radiológica más avanzada para el diagnóstico de esta malformación, ya que proporciona un enfoque más real en tres dimensiones de la invaginación y muestra datos radiológicos como dimensión, destrucción y oposición, además de la morfología interna anormal; por este motivo, se puede considerar que la TCHC es una herramienta más favorable para el diagnóstico y manejo ( 11,24 ).…”
Section: Imagenología Del Diente Invaginadounclassified
See 1 more Smart Citation